Development of Tourist Infrastructure Along the Great Silk Road (Journal of Geography and Environmental Management, 2018)
The article presents the development of the tourist infrastructure of the Kazakhstan part of the once existed Great Silk Road. Today Great Silk Road is one of the key long-term projects of the United Nations, aimed at revival and restoration of the trade and cultural relations between East and West. The authors calculate the index of the tourist infrastructure of the transport corridor zone. The chosen methodology is complemented by an analysis of the qualitative indicators of the development of the tourist infrastructure, obtained with the help of expert assessments, the results of a survey conducted among both tourists and tourism enterprises. As a result of the research we determined that the whole Tourism Infrastructure of the transport corridor “Western Europe - Western China” consists of 6181 objects. The average value of the quantity of the objects of Tourism Infrastructure per 100 kilometers along the entire corridor amounts to 222 objects. The high level of development of Tourism Infrastructure is held fix in the zone along the road of Almaty oblast, which occupies the leading position in most components of the Index. In this case, the Index amounted to 372,9. None of the zones along the road of the transport corridor was included into the level of the rank above average. The study made it possible to identify problems that hamper the development of tourism infrastructure in the regions: primarily related to the state of the material and technical base and administrative and legal problems.